Flail Foot- Common presentation Of an Uncommon Disease - Nair, Poornima; Pillai, Rammohan Krishna (Nepal Journal of Neuroscience, 2001)
Neurosyphilis is classically associated with meningovascular syphilis in the acute-subacute stage and tabes dorsalis & dementiaparalytica in later stages. But cases presenting as demyelinating polyradiculoneuropathy are uncommon. A 27 yr old male presentedwith ascending polyneuropathy with electrodiagnostic testing consistent with Guillain-Barre Syndrome (GBS).He had CSF VDRLTPHA positive, supporting a diagnosis of neurosyphilis associated with GBS.This case highlights the importance of consideringsyphilis in any patient presenting with acute polyradiculoneuropathy